Contact allergy to ingredients of topical medications: results of the European Surveillance System on Contact Allergies (ESSCA), 2009–2012. Issue 11 (28th July 2016) - Uter, Wolfgang; Spiewak, Radoslaw; Cooper, Susan M.; Wilkinson, Mark; Sánchez Pérez, Javier; Schnuch, Axel; Schuttelaar, Marie‐Louise
Abstract: Purpose: The aim of this study was to give an overview of the prevalence of contact allergy to active ingredients and excipients of topical medications across Europe. Methods: Retrospective analysis of data collected by the European Surveillance System on Contact Allergies (www.essca‐dc.org ) with substances applied to consecutively patch tested patients, 2009–2012, in 54 departments in 12 European countries. Results: In view of the varying composition of the baseline series used in the previously mentioned departments and countries, between 58 833 (lanolin alcohols) and 16 498 patients (sodium metabisulfite) were patch tested with the topical agents covered in this study. Among these, positive (allergic) reactions were most commonly observed to sodium metabisulfite (3.12% positive), followed by propolis (2.48%), Compositae mix (1.73%), lanolin alcohols (1.65%) and caine mix III (benzocaine, cinchocaine and tetracaine; 1.27%). Conclusions: Several of the substances warrant routine screening for contact allergy, i.e. patch testing in a baseline series. However, in view of a vast number of other topical agents, additional patch testing with the suspect topical drug preparations (including natural remedies and cosmetics) is warranted. In the event of a positive test to the (pharmaceutical) product, single ingredients should be tested individually to precisely identify the hapten(s). Copyright © 2016 John Wiley & Sons, Ltd.